Performance Characteristics Of EDFAs In Different Types Of System Configurations - Pathmanathan, Shankar (2009)
In this dissertation, the basic concepts of modelling the EDFA characteristics are presented. The rate equations and the propagation equations are discussed. Then the solutions to this set of non-linear coupled differential equations are carried out numerically via the forth-order Runge-Kutta method, and the associated boundry value problem is solved by using the relaxation method. The results show the important device performance characteristics of gain and noise figure with respect to the three main input design parameters - pump power, signal wavelength and input signal power.